Architectural Envelope Systems Based on Triply Periodic Minimal Surfaces. Issue 4 (December 2014) - Sierra, Fernando; Rodriguez, Carolina M.
This paper presents the results of a research project, which explores Triply Periodic Minimal Surfaces (TPMS) as a source of inspiration for the design of interior architectural envelopes. TPMS are a large family of surfaces that are not yet fully discovered. This work begins by identifying the members of this family which geometrical characteristics and growth patterns show potential for applications in interior architecture; this selection is made by means of a geometric analysis of these surfaces. The central part of the paper proposes three alternative manufacturing techniques for built approximations of TPMS: ruled surfaces, discrete surfaces and warped surfaces. These were then tested in the development of three modular systems of perforated and permeable surfaces, which were designed using simple construction methods intended to be replicable in different contexts. The components of the systems were manufactured with recyclable and recycled materials (i.e. waste products) and employing local tools and technical resources. The results of this research aim to highlight and explore the formal and geometric benefits of TPMS in the design of architectural components. The main advantages identified in the proposed systems relate to acoustic properties, structural performance and constructional process. It is suggested that the contributions of this research can be used both for educational purposes within academia and commercial purposes in future developments of the systems.